Design Analysis and Implementation of a Passive Expansion Spherical Robot - Shao Pai; Qin Jianjun; Cao Yu; Liu Xingjie; Chen Haonan (Jixie chuandong)
A linear deployable gear and rack mechanism is introduced. In order to improve the maneuverability and obstacle-crossing performance of the spherical robot in different scenarios such as narrow space, complex terrain and bumpy road, a passive expanded single-degree of freedom mechanism is used to expand the expanded radius to improve the obstacle-crossing performance. A linear expanded rack-and-pinion mechanism is introduced to design a spherical robot with compact structure and multiple motion modes. Mathematical models are established to perform kinematic and dynamic analysis of spherical robot mechanisms, the simulation results of rolling and obstacle crossing are compared with the theoretical values to verify the correctness of kinematics and dynamics. On this basis, the prototype is made to further verify the feasibility of the mechanism, and verify that the mechanism has strong mobility and obstacle crossing ability.